Eco-MagneTech Playground: A Prototype for Integrating STEM and Sustainability in Primary Education - Surendren, Nievesh Nair; Karupaiah, Thiyagu (PPSDP International Journal of Education, 2026)
A conceptual prototype that integrates STEM learning for primary school students is needed. In this study, a prototype demonstration approach was employed using Eco-MagneTech Playground, involving 32 primary school students aged 12 from a school in the Kinta Utara District. This study employed a qualitative research method. The design and development of the Eco-MagneTech Playground incorporated elements such as solar-powered streetlights, magnetic playground concepts, and a conceptual anti-cosmic radiation jogging track. The findings revealed notable student engagement, and students’ understanding of renewable energy and magnetism. Students’ questioning skill and evaluative skill provided evidence of emerging critical thinking skills. The Eco-MagneTech Playground is highly potential as an alternative tool to traditional textbook-based science teaching and learning. Unlike traditional classroom-based learning, the Eco-MagneTech Playground promotes active learning and critical thinking among primary school students. It also offers teachers an engaging approach to integrating STEM education through play-based learning environments. Further recommendations for future research were also suggested.